Structure and hydrogen bonding interactions in methoxysalicylaldehyde thiosemicarbazone derivatives in solution by NMR and DFT methods - Novak, Predrag; Pičuljan, Katarina; Hrenar, Tomica; Smrečki, Vilko (2009)
Summary: Solution state structure and hydrogen bonding in 4- and 5-methoxysalicylaldehyde 4-phenyl-thiosemicarbazones, 1 and 2, have been studied by a combined use of NMR spectroscopy and DFT calculations. It has been shown that both compounds existed in hydroxy-thione tautomeric form in solution as previously found in solid state. Two kinds of hydrogen bonds were found to exist in solution, i.e. intra- and inter-molecular. DFT calculations and chemical shift values support the conclusion that three center hydrogen bonds were formed between the studied compounds and the solvent used, involving OH and NH groups. The solution state structures of 1 and 2 were found to differ slightly from those observed in the solid state which was attributed to a low barrier of rotation around the N–N bond
Bibliografija: 22 jed
Keywords: Vodikova veza -- NMR metoda -- DFT metoda -- Molekulska struktura